Analysis of time-varying friction excitations in helical gears with refined general formulation. (September 2015) - Jiang, Hanjun
Time-varying sliding friction force and friction torque are regarded as non-negligible excitation sources of vibration and noise in gears. The sliding friction force primarily excites the motion along the off-line-of-action direction, which transmits vibration to the housing through shafts and bearings and then radiates noise. Since the contact line intersects with the pitch line, and the directions of the friction forces are opposite on both sides of the pitch line, the calculation of the friction excitations in helical gears becomes more difficult, especially in the high contact ratio helical gears. However, there is no universal method for calculating the friction excitations in helical gears with different range of contact ratio. The changes of friction excitations in helical gears are highly dependent on the geometric parameters such as helix angle and face width among others. Yet, there exist very limited studies on these topics. In this study, a refined general formulation for the calculation of time-varying contact line and friction excitations is proposed by assuming uniform load distribution along the contact lines with time-varying normal force and friction coefficient. Key gear parameters such as modification coefficient, helix angle, and face width are analyzed to illustrate their effects on the time-varying contact line and friction excitations. The results demonstrate that the refined general formulation is effective for the calculation of the friction excitations in helical gears with different range of contact ratio, and the parametric analysis could supply some guidance for choosing gear parameters in the design of helical gears to reduce the friction excitations.